Physical activity promotion at the local level : municipal sport authorities participation in Colombia - Rozo-Salazar, Daniela (2014)
Physical activity promotion (PAP) has reached policy agendas worldwide due to the social and economic burden that non-communicable diseases have generated. Colombia is one of the countries that have taken the challenge of promoting healthy lifestyles in order to reduce this burden and in addition, take advantage of other benefits that promoting this healthy lifestyle brings. Although some research has been done on the field, no studies related to the local government contribution were found. The local government plays a crucial role in PAP, considering that it has a great influence on the physical and social environment of a city and consequently in the individual behavior of its citizens. Additionally, it has a great responsibility concerning public health, social and economic development and environmental sustainability, aspects that are related to PAP.